Short implants - When, where and how? - Anjan Kumar Shah (Wolters Kluwer Medknow Publications, 2015)
The success of dental implants has led to research in techniques in minimising surgical complexity and increasing survival. Short dental implants are increasingly being seen as an alternative to more extensive bone augmentation procedures. This paper reviews aspects of short implant literature to give some guidelines in making their use more successful.